Childhood anxiety trajectories and adolescent disordered eating: Findings from the NICHD study of early child care and youth development. Issue 7 (17th June 2014) - Zerwas, Stephanie; Holle, Ann Von; Watson, Hunna; Gottfredson, Nisha; Bulik, Cynthia M.; Weissman, Ruth Striegel; Klump, Kelly; Steiger, Howard; Tanofsky‐Kraff, Marian
ABSTRACT Objective The goal of the present article was to examine whether childhood anxiety trajectories predict eating psychopathology. We predicted that girls with trajectories of increasing anxiety across childhood would have significantly greater risk of disordered eating in adolescence in comparison to girls with stable or decreasing trajectories of anxiety over childhood. Method Data were collected as part of the prospective longitudinal NICHD Study of Early Child Care and Youth Development (N = 450 girls). Childhood anxiety was assessed yearly (54 months through 6th grade) via maternal report on the Child Behavior Checklist. Disordered eating behaviors were assessed at age 15 via adolescent self‐report on the Eating Attitudes Test (EAT‐26). We conducted latent growth mixture modeling to define girls' childhood anxiety trajectories. Maternal sensitivity, maternal postpartum depression, maternal anxiety, and child temperament were included as predictors of trajectory membership. Results The best fitting model included three trajectories of childhood anxiety, the low‐decreasing class (22.9% of girls), the high‐increasing class (35.4%), and the high‐decreasing class (41.6%). Mothers with more symptoms of depression and separation anxiety had girls who were significantly more likely to belong to the high‐increasing anxiety trajectory. There were no significant differences in adolescent disordered eating for girls across the three childhood anxiety trajectories. Discussion Childhood anxiety, as captured by maternal report, may not be the most robust predictor of adolescent disordered eating and may be of limited utility for prevention programs that aim to identify children in the community at greatest risk for disordered eating. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:784–792)